MATERIALISME SEBAGAI PEMODERASI PENGARUH CINTA UANG TERHADAP KECENDERUNGAN KECURANGAN DANA DESA - Kase, Marce Sherly; Redjo, Paulina Rosna Dewi (Universitas Katolik Indonesia Atma Jaya, 2025)
We conducted this research to examine the moderating effect of materialism variables on the impact of the love of money on the tendency to cheat village funds. The quantitative design used is scientific research characterized as systematic. It tests the causality of the relationship between parts and characteristics. This research was conducted in 12 villages in the West Insana sub-district of North Central Timor Regency. The source data is fundamental data obtained directly from respondents. The data collection method is a questionnaire survey where respondents provide answers directly. The population is categorized as village officials in the West Insana sub-district with a sample size of 36 village government officials with the authority to manage village finances. These were determined using purposive non-probability sampling. The research utilized Moderated Regression Analysis (MRA) or moderated regression analysis. This research found that materialism could not act as a moderating variable in the effect of love of money on the tendency to cheat village funds. The implications of this research for the local government of North Central Timor Regency are to provide financial education on how to work on village financial reports per applicable accounting standards and to include village officials in village management training activities, especially village asset management.